2017
DOI: 10.3390/mi8070207
|View full text |Cite
|
Sign up to set email alerts
|

Electroceutical Approach for Impairing the Motility of Pathogenic Bacterium Using a Microfluidic Platform

Abstract: Electrotaxis, or galvanotaxis, refers to the migration pattern of cells induced in response to electrical potential. Electrotaxis has not been explored in detail in bacterial cells; information regarding the impact of current on pathogenic bacteria is severely lacking. Using microfluidic platforms and optical microscopy, we designed a series of single- and multi-cue experiments to assess the impact of varying electrical currents and acetic acid concentrations on bacterial motility dynamics in pathogenic multi-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…For example, several studies were executed regarding the motility of P. aeruginosa in the presence of an electric field using microfluidic devices. The authors found that bacteria were attracted to the anode and repelled by the cathode, and that the movement diameter of P. aeruginosa was influenced by the strength of the electric field [ 110 ]. On the other hand, studies that utilized microscopy to observe the motility of P. aeruginosa found that its walking pattern depended on the motility of its type IV pili.…”
Section: Resultsmentioning
confidence: 99%
“…For example, several studies were executed regarding the motility of P. aeruginosa in the presence of an electric field using microfluidic devices. The authors found that bacteria were attracted to the anode and repelled by the cathode, and that the movement diameter of P. aeruginosa was influenced by the strength of the electric field [ 110 ]. On the other hand, studies that utilized microscopy to observe the motility of P. aeruginosa found that its walking pattern depended on the motility of its type IV pili.…”
Section: Resultsmentioning
confidence: 99%